METHODS FOR THE DEVELOPMENT OF PHYSICAL QUALITIES OF STUDENTS - Golibjon Nematovich Ernazarov (Western European Studies, 2024)
The article will tell about the method of circular exercises in the acquisition and education of physical qualities of students, based on their physical fitness and physical qualities. When insufficient attention is paid to the complex of circular exercises in the traditional organization of the physical education process, opposite situations are observed in the approach to exercises. For this reason, despite the fact that a number of studies have been conducted, the expected result has not yet been achieved. The theoretical and practical solution of the revealed contradictions requires the preparation of additional scientific, scientific and methodological developments on the methodology of physical development based on the use of an improved method of circular exercises, taking into account the physical qualities of students of higher educational institutions, individual characteristics of their body and adequate content of motor activity.
Keywords: immunity; physical performance; physical fitness